Effects of the microsporidium Nosema pyrausta (Microsporida: Nosematidae) on the egg parasitoid, Trichogramma nubilale (Hymenoptera: Trichogrammatidae) - Sajap, Ahmad Said; Lewis, L. C. (Elsevier, 1988)
Trichogramma nubilale developing in Nosema pyrausta-infected eggs of the European corn borer, Ostrinia nubilalis, were directly affected by the microsporidium. Microsporidian spores, which were confined to the gut lumen in the larval stage, were found in the adjacent tissues of the gut epithelium, muscle, and nervous system of the pupal and adult stages. This infection resulted in a significantly reduced adult emergence rate and fecundity of the parasitoid.